Gratitude dan body image perempuan emerging adulthood yang pernah mengalami body shaming - Samatha, Vania Christika; Hapsari, Elisabet Widyaning (Jurnal Psikologi Poseidon, 2024)
Abstract. One of the things that individuals focused on in emerging adulthood was their physical appearance and their concern for body image. Body image was a person's perception of their body. This study aimed to look at the relationship between gratitude and body image. Participants in this study totaled 99 women (Mean age 20.64 / SD age 1.81) in emerging adulthood who had experienced body shaming. The sampling technique in this study was purposive sampling. The research instrument used gratitude and body image scales. The data analysis technique used in this study was product moment correlation. The results showed a positive relationship between gratitude and body image with a correlation value of 0.289 and p = 0.004 (p < 0.05) with an effective contribution of 8.3%. That is, the higher the gratitude, the more positive the body image would be. The results of the study could be used as an intervention design.